Anova dan Tukey HSD Analisis Kesalahan Siswa dalam Menjawab Soal Cerita Matematika Berdasarkan Kriteria Watson - Febriani, Suci; Astuti; Ediputra, Kasman; Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Error Analysis is a technique to identify, classify and interpret systematically the mistakes made by students who are learning to find out the circumstances, causes and various other aspects that are in it. This study analyzes the types of errors made by students in working on mathematics story problems based on Watson's criteria in class IX students of SMP Negeri 1 Bangkinang Kota. The purpose of this study was to see if there was a significant comparison of the results of the 9th grade Mathematics daily test. Before conducting the ANOVA test, first the data normalization test is carried out, then the homogeneity test and then conduct the ANOVA test. The ANOVA test used in this study is a one-way ANOVA test. After testing the data on the results of the daily test scores of Mathematics class IX SMP Negeri 1 Bangkinang Kota, the data obtained from the daily test scores of class IX B, class IX I, class IX J which means that the average daily test scores of the five classes do not have significant differences. In other words, the average daily test scores of class IX B, class IX I, class IX H are the same. There is data on the daily test scores of class IX I, class IX H, class IX F which means that the average daily test scores of the three classes are the same.